Synaptic engineering: an ionic switch of C.elegans behavior - Rayes, Diego Hernán (2014)
Mapping the neural connections of nervous systems is often considered to be a fundamental step in understanding behavior. However, a neural connectivity map carries no information about the activity of neurons and the nature of the connections that each neuron makes. Neurons are embedded in neural networks, which require a delicate balance between excitation and inhibition to maintain network stability. Homeostatic processes, conserved from invertebrates to humans, can adjust synaptic and neuronal excitability to keep neural circuits functioning within their stable dynamic range. In these circuits, ligand-gated ion channels (LGICs) are the principal signaling components that mediate fast inhibitory and excitatory neurotransmission. Is it possible to reverse the behavioral output of a neural circuit by changing the ion selectivity of LGICs and the sign of a synapse? Do intrinsic developmental constraints or homeostatic and behavioral feedback mechanisms prevent switches in the sign of a synapse within a network? We are interested in addressing these questions using the neuronal circuit that mediates the escape response of the nematode Caenorhabditis elegans, the only animal with a completely defined neural wiring diagram . In this circuit tyraminergic neurons coordinate the suppression of head movements with backward locomotion through the activation of a group of Cys-loop biogenic amine-gated chloride channels recently described, the LGCCs. We analyzed the molecular and behavioral consequences of changing the ion selectivity of one of these LGCCs, LGC-55, from anionic to cationic. Our data show that the C. elegans connectome is established independently of the nature of synaptic activity or behavioral output and suggest that switches in LGIC ion selectivity could provide an evolutionary mechanism to change behavior.